Human papillomavirus and endometrial cancer (review of literature and meta-analysis) - M. К. Ibragimova; E. V. Kokorina; М. M. Tsyganov; О. N. Churuksaeva; N. V. Litviakov (Опухоли женской репродуктивной системы)
The important role of human papillomavirus (HPV) of high carcinogenic risk in the emergence and development of cervical cancer is undeniable. Approximately 90 % of cases of verified cervical cancer are HPV positive. The level of infection with this virus exceeds that of gonococci, chlamydia and yeast infections. Currently, one of the most discussed issues is the possibility of the association of HPV with the risk of developing malignant neoplasms when localized in organs that are anatomically close to the cervix. One of these localizations is the body of the uterus. It is known that endometrial cancer is based on its pronounced hormone dependence. Nevertheless, many factors are involved in the carcinogenesis of endometrial neoplasms, including genetic and epigenetic disorders, as well as risk factors, which include alimentary, hormonal, hereditary causes. At the same time, a controversial issue is the involvement of HPV in the development of this type of cancer. The data on the presence of HPV in endometrial cancer are extremely contradictory: the researchers claim both the complete absence of the effect of the virus on the development of this type of cancer, and the detection of HPV in 60–80 % of cases of tumors. In this regard, it becomes necessary to systematize the currently available research results on this issue and to conduct a meta-analysis of the association of HPV infection with the risk of endometrial cancer.